STRATEGI PENGEMBANGAN DESA BERBASIS PEMETAAN WILAYAH DAN POTENSI LOKAL - Rafli Jen Saputra; Livia Tria Ananda Pane; Dinda Putri Roza; Dhea Ananda; Ar Rafi Agus; Ridwan; Miftahul Khair (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The regional mapping activity in Nagari Koto Gadang Anam Koto was conducted to strengthen the village’s capacity in managing its territory and planning development based on accurate spatial data. The main objective of this activity was to produce a standardized administrative map that can be used as a reference by village officials and the community. The implementation process began with field observations and identification of territorial boundaries together with village officials and local residents. Data processing was carried out using Geographic Information System (GIS) software for digitizing, overlay analysis, and map layout preparation, which was then revalidated with the village government.The result of this activity is an administrative map containing information on village administrative boundaries, road networks, infrastructure, and important points such as public facilities, places of worship, and tourist attractions. The availability of this map helps the village government understand the area more comprehensively, formulate development plans, and improve public services. Therefore, this regional mapping activity not only produces a technical document but also serves as a strategic instrument to promote community empowerment in Nagari Koto Gadang Anam Koto